Bioconcentration, elimination and effects of fire foam-related poly- and perfluoroalkyl substances in brown trout (Salmo trutta) - Johanson, Silje Modahl (2015)
Poly- and perfluoroalkyl substances (PFASs) are anthropogenic and persistent chemicals used as surfactants in many applications, including aqueous film-forming foams (AFFFs, fire foams). Regular training exercises utilising AFFFs have led to the direct releases of PFASs into the environment and subsequently a global distribution of the compounds. PFAS contamination of soil and water has been reported around multiple Norwegian airports such as in the lake Lavangsvatnet near Harstad/Narvik Airport Evenes. This study aimed to quantify the bioconcentration, elimination and effects of selected fire foam-related PFASs on biomarkers for the induction of metabolic enzymes (ethoxyresorufin O-deethylase), oxidative damage (lipid peroxidation and peroxisomal acyl-CoA oxidase) and liver damage (alanine aminotransferase). Juvenile brown trout (Salmo trutta) were exposed through water to two levels of a PFAS mixture (PFOS, PFHxS, 6:2 FTS, PFPeA, PFHxA and PFOA) for three weeks. The low PFAS concentrations (10 µg/L total PFASs) were made to resemble the levels of contamination detected in Lavangsvatnet. The exposure period was followed by a depuration period of ten weeks. Only PFOS and PFHxS were detected in a large proportion of the trout sampled during exposure and depuration. Both the compounds bioconcentrated significantly in trout exposed to the high concentration (785 µg/L total PFASs); however, only PFHxS were significantly increasing during the exposure period in fish from the low treatment. Bioconcentration factors were calculated to be 244 and 185 L/kg for PFOS, and 6.34 and 11.2 L/kg for PFHxS in trout from the high and low treatments, respectively. PFOS did not appear to be eliminated following the ten weeks of depuration. The concentrations of PFHxS decreased significantly during the depuration period in trout from the high treatment, and the half-life of this compound was estimated to 2.3 weeks. Activity of the CYP1A enzyme (by the analysis of ethoxyresorufin O-deethylase activity) in gills was increased in trout exposed to the low concentration of PFASs ten weeks after terminated exposure. Neither biomarkers for oxidative damage nor liver damage were significantly affected in the trout. Differences in the sensitivity to PFOS and PFHxS have previously been documented between various species. Based on the results presented in this study, the PFAS contamination in Lavangsvatnet would not be expected to cause oxidative damage or liver damage in the population of trout inhabiting this lake. PFOS would, however, be expected to reside in the trout and induce the activity of CYP1A in gills a while after terminated exposure.